Increasing MSME productivity and implementation of business financial applications in Hegar Manah Village - Parulian; Darma, Yuki Dwi (Central Community Development Journal, 2021)
Increasing the productivity of MSMEs through the creation of innovative products and the application of village finance applications is a theme raised at Pelita Bangsa university community service. In this service, it is expected to be able to understand every problem that occurs in the community and make the best decisions to be able to solve these problems with creative ideas. Hegar Manah Village is located in West Java, Bekasi Regency, East Cikarang District. The livelihoods of the Hegar Manah village community are in the agricultural, trade, MSME, livestock and fisheries sectors. The most prominent potential in Hegar Manah village is in the MSME sector, in this MSME the Hegar Manah community is able to create products, namely in the food sector such as apem cakes, lunkhead, wet cakes, pastries, and various other types of pastries of superior quality.